Family policies in the context of low fertility and social structure - Thomas Fent; Belinda Aparicio Diaz; Alexia Prskawetz (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2011)
The aim of this paper is to analyse the effectivity of family policies in the context of different assumptions regarding the social structure of a society. We use an agent based simulation model to analyse the impact of family policies on individual fertility decisions and on cohort fertility, intended fertility, and the fertility gap on the aggregate level. The crucial features of our simulation model are the agents' heterogeneity with respect to age, income, parity, and intended fertility, the social network and social influence. Our results indicate that both fixed and income dependent child supports have a positive and significant impact on fertility. However, several network and social influence parameters have the ability not only to influence fertility itself but also the effectivity of family policies. Therefore, policymakers aiming to transfer a certain policy mix that has proved successful from one country to another one ignoring differences in the social structure may fail. Family policies can only be successful if they explicitly take into account the characteristics of the society they are assigned for.
Keywords: 300; Familienpolitik; Fertilität; Soziales Netzwerk; Sozialstruktur; Agentenbasierte Modellierung; Theorie